Mongolia’s Proposed Sovereign Wealth Fund in the Broader Fiscal Framework - World Bank (Washington, DC : World Bank, 2022)
The government of Mongolia has presented the creation of a new sovereign wealth fund designed to invest in domestic assets, to be managed in whole or in part by state-owned mining enterprise Erdenes Mongol. This new fund will supplement existing extrabudgetary institutions with various macroeconomic and industrial policy objectives, namely the Development Bank of Mongolia LLC, the Future Heritage Fund, and the Fiscal Stability Fund. The fund’s mandate - and consequently its deposit rules, withdrawal rules, and investment guidelines - remain unclear. The fund is being established in a unique macroeconomic and fiscal environment. This brief aims to describe the Mongolian context so that the new sovereign wealth fund can be designed to fit into the existing fiscal framework rather than undermine public financial management systems and public accountability. The brief then provides a set of lessons for the design of strategic investment funds, drawn from case studies around the world.